Vaccines in Mediterranean aquaculture: practice and needs - Le Breton A.D. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
Commercial conventional vaccines, which have proved their efficacy under laboratory conditions and in field trials, are available for the main bacterial diseases threatening marine finfish productions in the Mediterranean. New technologies can help develop more efficient vaccines or products for emerging diseases but regulatory aspects are still limiting their field of application. The claims of unsuccessful vaccination using a commercial vaccine should be investigated with a proper diagnosis of the resulting mortality. This approach shows in most cases that the vaccine itself is not at fault, since the vaccination strategy applied was not properly adapted to the farming conditions on site, to the disease considered and its epidemiology or the species needing protection. Vaccination programmes represent only one part of health management and should be applied parallel to other prophylactic methods, such as sanitary rules to optimize production results.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)